The Impact of Coding Apps to Support Young Children in Computational Thinking and Computational Fluency. A Literature Review - Papadakis, Stamatis (Frontiers in Education, 2021)
Data that shows that young age children can learn and acquire CT and coding skills has led governments and policymakers internationally to integrate CT into the curriculum, starting in the earliest grades. Apps offering various programming lessons, puzzles, and challenges to teach core coding concepts to children have gained increased popularity in recent years. Coupled with the media and government's rhetoric and an increasing number of coding apps, educators have been responsible for introducing young children to coding using touchscreen technology. Nevertheless, few apps have been evaluated for their effectiveness, so we know little about what children can learn from them. Further research is required to determine whether the available coding apps are developmentally appropriate, appealing, and meaningful for young children, helping them develop CT, coding, and general skills. This article presents a literature review on how coding apps affect young children's CT, coding, and general literacy skills. The literature review includes 21 studies that examined four different apps. The main conclusion is that all apps positively affect the development of children's CT and coding skills. However, ScratchJr seems to be the most useful app.